Techniques for signal to noise ratio adaptation in infared optical wireless for optimisation of receiver performance - Abdullah, Mohammad Faiz Liew (2006)
The challenge of creating a new environment of links for wireless infrared and optical local area networks CLANs) is driving new innovations in the design of optical transceivers. This thesis is concemed with a systematic approach to the design of receivers for indoor optical wireless communication. In particular, it is concemed with how to offer bandwidth adjustment capability in a receiver according to the dynamic service quality of the incoming signals. Another part of the discussion of the thesis is how one can properly choose the front-end preamplifier and biasing circuitry for the photodetector. Also, comparison is made between different types of amplifier, and the methods of bandwidth enhancement. The designs of six different teclmiques of integrating transimpedance amplifiers, with photo detectors to adapt an adjustable bandwidth control receiver are discussed. The proposed topologies provide an adjustable range of bandwidths for different frequency ranges, typically between 52Hz to 115MHz. The composite technique designs were used to incorporate into a system with an automatic gain control to study its effect, on an optical wireless receiver which had bandwidth adjustment and automatic gain adjustment. Theoretical analysis of noise perfom1ance for all the designed circuits is also presented. The theory and design of obstacles of indoor optical wireless receiver delivery, in addition to techniques for mitigating these effects, are discussed. This shows that infrared is a viable altemative to radio for certain applications.